2015
DOI: 10.1016/j.jep.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

In vitro opioid receptor affinity and in vivo behavioral studies of Nelumbo nucifera flower

Abstract: Ethnopharmacological relevance Nelumbo nucifera Geartn., known as sacred lotus, has been used traditionally in South East Asia as a traditional medicine for various CNS disorders including stress, fever, depression, insomnia, and cognitive conditions. Aim of the study To investigate the in vitro cannabinoid and opioid receptor binding affinities, and in vivo behavioral actions of Nelumbo flower extracts and to isolate the potential compounds to treat CNS associated disorders. Materials and methods The whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Furthermore, it was demonstrated that a complete reversion of neurological benefits were detected after selective blocking of the cannabinoid 1 receptor (CB1) with a selective CB1 receptor antagonist. In another study, the South East Asian traditional medicine from the sacred lotus flower extracts ( Nelumbo nucifera ) was subjected to in vitro cannabinoid and opioid receptor radioligand binding assays, functional GTPγS assays and in vivo behavioral evaluations in mice [ 45 ]. The N. nucifera compounds O -methylcoclaurine, N -methylcoclauirine, coclaurine, and neferine displayed various degrees of opioid receptor affinities in vitro.…”
Section: Effect Of Plant Extracts On Cns Receptors and Therapeuticmentioning
confidence: 99%
“…Furthermore, it was demonstrated that a complete reversion of neurological benefits were detected after selective blocking of the cannabinoid 1 receptor (CB1) with a selective CB1 receptor antagonist. In another study, the South East Asian traditional medicine from the sacred lotus flower extracts ( Nelumbo nucifera ) was subjected to in vitro cannabinoid and opioid receptor radioligand binding assays, functional GTPγS assays and in vivo behavioral evaluations in mice [ 45 ]. The N. nucifera compounds O -methylcoclaurine, N -methylcoclauirine, coclaurine, and neferine displayed various degrees of opioid receptor affinities in vitro.…”
Section: Effect Of Plant Extracts On Cns Receptors and Therapeuticmentioning
confidence: 99%
“…All ten compounds were tested for cannabinoid activity with CB1 and/or CB2 receptors. 22 As shown in Table 2, the initial testing of (-)- 3a-c against CB1 and CB2 receptors showed that octahydrochromene (-)- 3c , containing an olefin at the C-4 position was marginally active, whereas both chromenols (-)- 3b and (-)- 3a , were inactive. Similarly, compound (+)- 5a , the product of the one-pot ene, Prins reaction of citronellal, was also inactive.…”
Section: Resultsmentioning
confidence: 99%
“…Salvindolin met the 70% threshold for advancement to the secondary assay and was subsequently evaluated in the secondary binding affinity assay that utilized a 12-step serial dilution from 100 μM to 0.5 nM to calculate the equilibrium dissociation constant (K i ). Further, salvindolin was evaluated for functional activity utilizing a [ 35 S]GTPγS binding assay (Kumarihamy et al 2015).…”
Section: Methodsmentioning
confidence: 99%